Analysing The Need for Innovative Staff Attendance Tracking System and Designing a Solution for Institut Bakti Nusantara - Tri, Susilowati; Sri, Hartati; Taufik, .; Adi Prasetya, Nanda (INTI International University, 2024)
Attendance at an educational institution or company is important in measuring the performance and attendance of lecturers. Manual attendance at the Institut Bakti Nusantara (IBN) is still a major problem, such as time time-consuming and prone to human error. Therefore, this study aims to analyse the need for an innovative attendance tracking system and design a solution using a QR Code application for the attendance of lecturers at the IBN. Using the waterfall method which includes the stages of needs analysis, system design, application development using QR Code technology, and application testing to test system functionality. The results of this study indicate that the QR Code Presence application developed can run well according to its function such as recording the attendance of Lecturers and providing attendance reports. This study produces a product, the IBN Lecturer attendance QR Code web application that can record attendance and manage attendance data.